Brunelleschiani - Borsi, Franco; Morolli, Gabriela; Quinterio, Francisco (Roma : Officina edizion, 1979)
Estudio de los colaboradores en la obra de Brunelleschi: F. della Luna, A. di Lazzro, Salvi D'Andrea.
Keywords: ARQUITECTURA RENACENTISTA; RENACIMIENTO; ITALIA; ARQUITECTURA; HISTORIA; BRUNELLESCHI, FILIPPO